MINERALOGICAL AND HYDRAULIC CHARACTERISATION OF HISTORIC FLOTATION TAILINGS - Todor Angelov (Sustainable Extraction and Processing of Raw Materials Journal, 2022)
ABSTRACT. A composite flotation tailings sample from historic Medet tailings dam was characterised to understand occurrences of copper and hydraulic properties of the material and to determine if there is an economic benefit of its reprocessing using hydrometallurgical processes. Conventional ICP-OES multi-element scan and carbon and sulphur determination by Leco were followed by sequential copper assay and mineralogical analysis using the Tescan Integrated Mineral Analyser (TIMA) to identify the elemental composition, acid soluble copper and mineral abundance and liberation. The tailings sample contained 0.105% Cu, 0.41 % S and 0.05% C. The analysis of the gangue minerals showed that the bulk of the material is made up of plagioclase feldspar with moderate amounts of K-feldspars and small amounts of mica, chlorite and clay minerals. Copper minerals cuprite and chalcopyrite with minor amounts of covellite and bornite were observed in the mineralogical analysis of the sample by TIMA. Based on the sequential copper assays, it was estimated that approximately 59.8% of copper contained in the sample reports as acid soluble copper. To understand the flow behaviour in the material the main hydraulic properties like hydraulic conductivity and moisture retention capacity were determined.